Pengaruh Komunikasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Unit Collection Pada PT. Julo Teknologi Finansial Tangerang Selatan - Idriszal, Fikri Nopal; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Communication (X1) and Work Discipline (X2) on Employee Performance (Y) of the Teleoperation Unit at PT. Julo Financial Technology, South Tangerang. The method used is a quantitative method. The data sources for this research are in the form of questionnaires, documentation, observation and literature study. Data analysis used in this research is validity test, reliability test, classical assumption test, correlation coefficient, multiple linear regression test and significance testing including the R statistical test. Using SPSS version 21 software. The results of this research show that communication has a significant effect on employee performance with the regression equation Y = 27.292 + 0.338X1, a correlation value of 0.927, meaning that the two variables have a very strong level of relationship. The coefficient of determination value is 86.0% and the hypothesis test is tcount3.789> ttable2.001. Thus Ho is rejected and Ha is accepted, meaning that there is a significant influence of communication on employee performance. Work Discipline has a significant effect on employee performance with the regression equation Y = 27.957 + 0.202The coefficient of determination value was 92.3%, and the hypothesis test obtained tcount 3.509> ttable 2.001. Thus Ho2 is rejected and Ha3 is accepted, meaning that there is a significant influence of work discipline on employee performance. Communication and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 24.218 + 0.112 X1 + 0.197 X2. The correlation value is 0.936, meaning that the independent variable and the dependent variable have a strong level of relationship. The coefficient of determination value is 92.7% while the remaining 7.3% is influenced by other factors. Hypothesis testing obtained a value of 363.562> F-table 2.766. Thus Ho is rejected and Ha3 is accepted. This means that there is a significant simultaneous influence of communication and work discipline on employee performance